Reading rights - Bakran, Juraj; Gabriel, Dunja-Marija; Golub, Koraljka Lazić, Nikolaj (2000)
The right to knowledge isn't questionable, only the ability to fulfil that right. Especially by the people with special needs, disabled people, in our case sight impaired and blind persons. Therefore the authors will
talk about speech synthesis and ability to "read" books to sight impaired persons. The MBROLA speech synthesizer will be presented. Because nobody can deny any persons right to knowledge, the library and especially the National library has a duty to offer books to everybody who is interested in reading. The another thing that the authors will talk about is how to get books in digital form, which is needed for
speech synthesis. The whole idea is making peace between intellectual property (authors)
and right to knowledge (readers).
Projekt MZOS
ENG